CONCEPTUAL MODEL OF TRAINING HIGHLY QUALIFIED PERSONNEL USING INFORMATION AND COMMUNICATION TECHNOLOGIES - Malyshev, Vladimir (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The article is devoted to the study of foreign theory and experience in designing a system of training highly qualified personnel using information and communication technologies and comparing them with domestic specifics in this area. In response to the need for training highly qualified personnel capable of solving research and pedagogical tasks in key areas for the development of the state, the purpose of this comparative study was to identify relevant and verified parameters for designing a conceptual model of the system for training scientific and pedagogical personnel in graduate school using ICT tools. The research is based on the analysis of domestic and foreign scientific and pedagogical literature devoted to the problems of training graduate students using ICT tools. To obtain empirical data, we applied the method of integrated observation in the design, administration and development of the postgraduate educational program; questionnaire surveys of graduate students, research supervisors and members of the state examination commission and in-depth interviewing of experts in the field of training highly qualified personnel with subsequent content analysis of the data obtained. As a result, we analyzed and systematized, taking into account the specifics of the use of information and communication technologies, such aspects of training highly qualified personnel as: theoretical, methodological and methodological provisions, personal, professional and regulatory requirements for graduate students and scientific supervisors, implementation and administration of the educational process in graduate school, including against the background of conditions of remote interaction, features of intermediate and final assessment of the formation of competencies of graduate students. The study opens up significant prospects for the practical application of the results obtained in the educational process.